Analisis Menentukan Harga Jual Produk Minuman Dan Snack Café Komunikopi Sampang Madura - Ach. Sholahur Robany (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This study aims to determine the calculation of the cost of goods produced and the profit or not of the results of product sales. In the title of the thesis